A Heuristic Evaluation of the Usability of Non-Professionally Self-Translated Crochet Patterns - Lindberg, Sanni (My University, 2024)
This study consists of a heuristic evaluation of the usability of eleven non-professionally self-translated crochet patterns gathered from Ravelry.com. The aim of the study was to find out what kinds of usability problems occur in the research material and how well the chosen heuristic evaluation method suits the evaluation of crochet patterns. The results are meant to improve both crochet pattern translations and the heuristic evaluation process in the future. The study was conducted from the perspective of User-Centered Translation (UCT) developed by Suojanen, Koskinen and Tuominen (2012; 2015). The usability of the research material was evaluated using a list of eight revised heuristics by Suojanen and Tuominen (2015, 279): match between translation and specification, match between translation and users, match between translation and real world, match between translation and genre, consistency, legibility and readability, satisfaction, and match between source and target texts. These heuristics are based on the list of ten heuristics for user-centered translation by Suojanen, Koskinen and Tuominen (2015, 90). The first heuristic, match between translation and specification, was excluded because the specifications were not available. The severity of each discovered usability problem was further evaluated according to Nielsen’s (1994) severity ratings. A total of 164 problems were found, of which 23 (~14%) were deemed major and the other 141 (~86%) minor or cosmetic. The majority (51%) of the problems are related to heuristic 8, match between source and target texts. The second most common problems are related to heuristic 6, legibility and readability – especially readability affected by problems with fluency. The rest of the problems are quite evenly distributed between the remaining heuristics, with the exception of consistency, where no problems were identified. Many of the identified usability problems already exist in the source texts and have then been transferred to the target texts at the translation phase. The heuristic evaluation method suited the evaluation of crochet pattern usability quite well. A more concise list of six revised heuristics is suggested for future use, where the heuristics of consistency and satisfaction are removed. It is also suggested that more focus be put on modifying and using the heuristics to discover exceptionally usable solutions in addition to usability problems. This could lead to more applications for the heuristics in translator training and other contexts.
Keywords: self-translation, user-centered translation, heuristic evaluation, crochet patterns